(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In article the written scientific language and its language features is considered. The written scientific language is language of monographs, scientific articles, textbooks. Read is noted that an effective form of attaching of students to the scientific speech is professional Russian where students shall learn to read special literature, to fix, to arrange the bibliography, footnotes, references. Authors lit features of a scientific written language to which it is very important to pay attention when training students in independent creation of texts of scientific genres.